(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Safety is the most important aspect that needs to be considered in a hospital. There are several types of safety: patient safety, health personnel safety, building safety, equipment safety, green productivity, and hospital business safety. Building safety is determined to be the third common adverse event that occurred in hospital and affects directly to the safety of patients and health workers. Building safety in hospitals consists of electrical installations, fire and lightning protection, wastewater treatment plants, medical gas systems and medical vacuum, and elevator installation. A systematic review of problems and solutions to improve hospital building safety is expected to become a useful information for any health profession, engineers, and researchers. The purpose of this study is to identify the result of research on the implementation of building safety in the hospital. Some literature on adverse events and solutions from 2000-2019 was reviewed. The result shows various adverse events such as fall of the elevator, fire, damage electrical current which resulted in many victims. The result of this literature review can be a reference for hospitals to conduct evaluation and innovation in the implementation of building safety in hospitals.